Location choice of Spanish multinational firms in developing and transition economies. Issue 2 (4th March 2017) - Martí, Josep; Alguacil, Maite; Orts, Vicente
Abstract: In this paper, we use firm-level data to investigate how different host country characteristics affect the decision of Spanish multinational firms to locate in developing and transition countries, and whether these determinants change when looking at manufacturing or services firms. As a methodological novelty, we estimate both standard conditional logit models as well as other discrete choice models that allow us to account for the possibility that firms perceive some alternative destinations as being more similar (nested and mixed logit models). A better understanding of the relevance of local factors that determine the competitiveness of these economies in providing multinational firms with location advantages can guide policymakers in their attempt to attract foreign capital flows. This, however, has not been previously addressed by the empirical literature at a firm level and across sectors. Our results suggest that Spanish investments in developing and transition economies are mainly driven by market-seeking factors. They also confirm the relevance of the business and financial climate in the location decision of multinational firms. Finally, the estimations reveal differences between manufacturing and services foreign direct investments in several local factors, such as the agglomeration effects, skilled labour and financial risk.